2015
DOI: 10.5944/rppc.vol.19.num.3.2014.13905
|View full text |Cite
|
Sign up to set email alerts
|

Inducción de craving por comida mediante realidad virtual no inmersiva

Abstract: Resumen: La terapia de exposición a señales se ha propuesto como un tratamiento eficaz para las conductas de atracón al propiciar la extinción de la asociación entre los estímulos relacionados con la ingesta compulsiva y la respuesta de craving. El objetivo de este estudio es evaluar si la exposición a alimentos en entornos de realidad virtual (RV) es capaz de producir niveles de craving consistentes con diferencias individuales en craving-rasgo y craving-estado, de manera que puedan ser utilizados en programa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As expected, their results showed that women primed for food craving experienced higher levels of food craving when exposed to VR environments. Ferrer-Garcia and co-workers (Agliaro-Lopez et al, 2014;Ferrer-Garcia et al 2014) found that food cravings experienced by healthy participants in different VR contexts were related to craving trait and state assessed by the Food Craving Questionnaire-Trait and State (FCQ-T/S). Ledoux et al (2013) suggested that the modest effect of VR exposure in their study could have been due to the limited quality of the VR system used or to the fact that participants were exposed to just one context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, their results showed that women primed for food craving experienced higher levels of food craving when exposed to VR environments. Ferrer-Garcia and co-workers (Agliaro-Lopez et al, 2014;Ferrer-Garcia et al 2014) found that food cravings experienced by healthy participants in different VR contexts were related to craving trait and state assessed by the Food Craving Questionnaire-Trait and State (FCQ-T/S). Ledoux et al (2013) suggested that the modest effect of VR exposure in their study could have been due to the limited quality of the VR system used or to the fact that participants were exposed to just one context.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous results support this notion. Ferrer-Garcia and co-workers (Agliaro-Lopez et al, 2014;Ferrer-Garcia et al 2014) found that food cravings experienced by healthy participants in different VR contexts were related to craving trait and state assessed by the Food Craving Questionnaire-Trait and State (FCQ-T/S). In these studies, food craving experienced in the VR environments was mainly associated with high reactivity to food cues, a strong desire to eat at this very moment and being hungry right now, according to scores obtained on the subscales of the FCQ-T/S.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence of the ability of food-related VR-based environments to elicit anxiety and craving responses similar to those expected in real life in both healthy and clinical (i.e., patient with BN and BED) groups. [33][34][35][36][37][38][39][40] As previously described, 32 a randomized controlled trial was conducted to assess the efficacy of VR-CET as a secondlevel treatment for BN and BED patients. The study showed that both second-level treatments (VR-CBT vs. additional cognitive behavior therapy [A-CBT]) improved all dimensional measures of outcome (i.e., clinician-rated frequency of episodes of binge eating and purging, self-reported tendency to engage in episodes of uncontrollable overeating, drive for thinness (DT), body dissatisfaction [BD], anxiety, and food craving), but a better overall short-term outcome (i.e., at post-treatment) was observed in the VR-CET group, 32 with a significantly higher reduction in number of binge and purge episodes and self-reported tendency to engage in episodes of overeating, food craving, and anxiety than the A-CBT group.…”
mentioning
confidence: 99%